2013
DOI: 10.1155/2013/525673
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Optimization Calculations for the Elasticity of Gold at High Pressure

Abstract: We present embedded atom method based geometry optimization aspects of pressure effect on some elastic and mechanical properties of gold. During study, we determined the pressure dependency of equilibrium volume, typical cubic elastic constants, bulk modulus, shear modulus, young modulus, and elastic wave velocities of the considered metal with varying pressure between 0 GPa and 1000 GPa. Finally, we carried out a benchmark between our results and other available theoretical calculations and experimental data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The lattice constant for GaAs was set as a 0 = 5.66 Å which is slightly higher than the experimental lattice constant a exp = 5.65 Å. Dther details of applied StillingerWeber type potential and its modified parameterization procedure can be also found in Han and Bester 17 . Ot is also possible to optimize related structures at constant pressures (includes all internal and cell variables) and constant volume (unit cell remains frozen) with GULP [1,[13][14][15][16]18] . Constant pressure optimization was performed for GaAs in our survey.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lattice constant for GaAs was set as a 0 = 5.66 Å which is slightly higher than the experimental lattice constant a exp = 5.65 Å. Dther details of applied StillingerWeber type potential and its modified parameterization procedure can be also found in Han and Bester 17 . Ot is also possible to optimize related structures at constant pressures (includes all internal and cell variables) and constant volume (unit cell remains frozen) with GULP [1,[13][14][15][16]18] . Constant pressure optimization was performed for GaAs in our survey.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Constant pressure optimization was performed for GaAs in our survey. The geometry of cells was optimized by the Newton-Raphson method based on the Hessian matrix calculated from the second derivatives and Hessian matrix was recursively updated during optimization by using the BFGS [1,[13][14][15][16]18] algorithm. After setting the preconditions for the B3 crystal structure of GaAs, we adopted multiple runs at zero Kelvin temperature and checked the pressure ranges starting from 0 GPa up to 25 GPa.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because measuring elastic modulus of solids at high pressure is difficult, little is known about elasticity of solids at high pressure. Ultrasonic technology and Brillouin spectroscopy are two technologies used to measure mechanical properties under the influence of pressure [2,3]. These are used for modest pressure ranges.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Testing elemental Au and Ni, it is found that commonly used approximations to the exchange-correlation (xc) functional perform well, however, only either for Au or Ni but not for both of them at the same time (such as in any Au-Ni alloy). Fortunately, it has been found that the relative deviations of computed elastic constants C th ij and the lattice parameter a th from experimental data C exp ij and a exp , 22,23 i.e., DC ij ¼ (C th ij -C exp ij )/C exp ij and Da ¼ (a tha exp )/a exp , are anti-correlated (see Figure 4(a)). This anti-correlation trend (DC ij % À12.5 Da) is composition-independent as it includes results obtained for both elemental Ni and Au using different parametrizations of generalized gradient approximation (GGA) [24][25][26][27][28] and local density approximation (LDA) 29 to the xc-functional.…”
mentioning
confidence: 99%